Sorptive properties of microplastics extracted from cosmetics - Praveena, Sarva Mangala; Aris, Ahmad Zaharin (Springer, Cham, 2022)
Microplastics from cosmetics, also known as “microbeads,” have been classified as a contaminant of emerging concern and are a global threat to aquatic ecosystems. After usage, these microplastics are flushed into the wastewater system, likely evade filtration, and are ultimately released to the aquatic environment in treated effluent discharge. Wastewater is likely a major pathway for microplastics to enter the aquatic environment, be transported over long distances, persist in the environment, bioaccumulate in food webs, and endanger human health. This chapter provides an overview of microplastics extracted from cosmetics, their pathways to wastewater and the aquatic environment along with their pollutant sorption properties. Sorptive properties of microplastics extracted from cosmetics primarily involve physisorption between microplastic surfaces and hydrophobic organic pollutants. To date, most microplastic sorption studies have involved microplastic debris commonly present in the aquatic environment. These studies have demonstrated that microplastics act as a vector for multiple pollutants. However, limited studies have provided a quantitative understanding of organic and inorganic pollutant sorption of cosmetic microplastics. These limited quantitative studies found that microplastic surface area, hydrophobicity, buoyancy, and aggregation influenced pollutant sorption in the aquatic environment. Furthermore, microplastic-sorbed pollutants were ingested by organisms at each trophic level. Additionally, digestive fluids were responsible for promoting microplastic-sorbed pollutants leaching into tissue, leading to bioaccumulation. Limited understanding of microplastic-sorbed pollutants from cosmetics calls for more studies to bridge the knowledge gaps and inform risk assessment and policy development.